Allergy immunotherapy across the life cycle to promote active and healthy ageing: from research to policies. Issue 1 (December 2016) - Calderon, M.; Demoly, P.; Casale, T.; Akdis, C.; Bachert, C.; Bewick, M.; Bilò, B.; Bohle, B.; Bonini, S.; Bush, A.; Caimmi, D.; Canonica, G.; et al.
Abstract Allergic diseases often occur early in life and persist throughout life. This life-course perspective should be considered in allergen immunotherapy. In particular it is essential to understand whether this al treatment may be used in old age adults. The current paper was developed by a working group of AIRWAYS integrated care pathways for airways diseases, the model of chronic respiratory diseases of the European Innovation Partnership on active and healthy ageing (DG CONNECT and DG Santé). It considered (1) the political background, (2) the rationale for allergen immunotherapy across the life cycle, (3) the unmet needs for the treatment, in particular in preschool children and old age adults, (4) the strategic framework and the practical approach to synergize current initiatives in allergen immunotherapy, its mechanisms and the concept of active and healthy ageing.